Complexes of 1,8-bis(hydrazidomethylsulfonyl)octane and 1,10-bis(hydrazidomethylsulfonyl)decane with copper(II) - V.V. Neklyudov; G.A. Boos; M.M. Shulaeva; O.A. Lodochnikova; G.A. Chmutowa; E.P. Bulavina; R.R. Amirov (Учёные записки Казанского университета: Серия Естественные науки)
1,8-bis(hydrazidomethylsulfonyl)octane and 1,10-bis(hydrazidomethylsulfonyl)decane differ by hydrocarbon spacer length, solubility in water, and polymerization tendencies. They and their amides are known to be new antitubercular agents. The substances act as polydentate ligands; in the pH range of 4.5–5.0 and with copper(II), they form cationic mono- and binuclear complexes. Preparatively isolated copper complexes with each of the two compounds have different compositions, which also differ from the composition of complexes in the solution.